Pemberdayaan Masyarakat melalui Pemanfaatan Daun Insulin sebagai Produk Pangan Antidiabetes di PKK Cempaka Banjarbaru: Community Empowerment through on the Use of Insulin Leaves as Antidiabetic Food Products to PKK Group Cempaka Banjarbaru - Sayakti, Putri Indah; Restapaty, Ratna; Saputri, Revita; Setia, Lisa; Marliadi, Reny; Akbar, Depy Oktapian (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The quality of information on health, including knowledge of plants that may be used as diabetes medicine, has a significant effect on public concern for health. This activity aims to introduce the community to the benefits of insulin leaves and Amazon beans, along with their benefits for diabetes, through community empowerment activities. Community empowerment activities include training in developing superior products with economic value using insulin leaves and Amazon beans. The problems identified include residents' need for more knowledge and skills in processing food based on insulin leaf plants, especially regarding food processing with antidiabetics. The method of activity used is education on the efficacy of insulin leaf plants and Amazon beans thru a Group Discussion Forum (FDG) with PKK RT 30 RW 20 women of Cempaka Banjarbaru Village. Moreover, the Community Empowerment Team provided training in the preparation using insulin leaves and Amazon beans into straightforward preparations such as pudding, cookies, tea, simplistic, simple steeping, and packaging manufacturing. Individuals could convert processed food products into Cempaka village home industry products as a business opportunity, thereby increasing people's living environment.